Ali Baba and the forty thieves (London : Usborne, 2007)
This series of books combines good stories with easy reading text for children aged six to seven years and over who have just started reading alone. The series has been developed with Alison Kelly who is an expert in early reading
Keywords: Children's fiction; Children's stories; Children.s readers